The Influence of Parents on The Leadership of Children in The Family - As A Psychological Factor in Parenting (Eurasian Journal of Humanities and Social Sciences, 2022)
The article examines the influence of parents on the formation of a child as a leader. The main qualities that a leader should have are listed. In accordance with these qualities recommendations for parents on The article discusses the influence of parents on the development of leadership qualities in their child